Persuasive technologies in building support system to prevent non-communicable diseases caused by sedentary lifestyle - Pérez de Celis, Concepción (2014)
In this paper, we present the use of persuasion to help people who want to change their everyday behavior technologies. Méxmov and Lifestyle Change Recommender Systems (LSCS) ¡Camina!, are designed to reduce sedentary as prevention of non-communicable diseases.